Clinical Neuroimaging Using 7 T MRI: Challenges and Prospects. Issue 1 (4th December 2017) - Vargas, Maria Isabel; Martelli, Pascal; Xin, Lijing; Ipek, Ozlem; Grouiller, Frederic; Pittau, Francesca; Trampel, Robert; Gruetter, Rolf; Vulliemoz, Serge; Lazeyras, Francois
ABSTRACT: The aim of this article is to illustrate the principal challenges, from the medical and technical point of view, associated with the use of ultrahigh field (UHF) scanners in the clinical setting and to present available solutions to circumvent these limitations. We would like to show the differences between UHF scanners and those used routinely in clinical practice, the principal advantages, and disadvantages, the different UHFs that are ready be applied to routine clinical practice such as susceptibility‐weighted imaging, fluid‐attenuated inversion recovery, 3‐dimensional time of flight, magnetization‐prepared rapid acquisition gradient echo, magnetization‐prepared 2 rapid acquisition gradient echo, and diffusion‐weighted imaging, the technical principles of these sequences, and the particularities of advanced techniques such as diffusion tensor imaging, spectroscopy, and functional imaging at 7TMR. Finally, the main clinical applications in the field of the neuroradiology are discussed and the side effects are reported.